2019
DOI: 10.1177/0269215519835889
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation of lower limb motor function in patients with stroke: a systematic review and meta-analysis of randomized controlled trials

Abstract: Objective: The aim of this study was to evaluate the effects of repetitive transcranial magnetic stimulation (rTMS) on the post-stroke recovery of lower limb motor function. Data sources: We searched the databases of PubMed, Cochrane Library, and Embase. The randomized controlled trials were published by 25 January 2019. Review methods: We included randomized controlled trials that evaluated the effects of rTMS on lower limb motor recovery in patients with stroke. Two reviewers independently screened the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…In detail, the results included the following: seven studies for motor function, 6268 three for manual dexterity, 6971 three for walking and balance, 7274 three for spasticity, 64,75,76 six for dysphagia, 7782 five for aphasia, 8387 three for unilateral neglect, 8890 three for post-stroke depression and vascular depression, 66,91,92 one for cognitive function, 66 and one for CPSP. 93 The study by Graef and colleagues 64 included data on both motor function and spasticity and, therefore, the results were independently considered for both categories.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, the results included the following: seven studies for motor function, 6268 three for manual dexterity, 6971 three for walking and balance, 7274 three for spasticity, 64,75,76 six for dysphagia, 7782 five for aphasia, 8387 three for unilateral neglect, 8890 three for post-stroke depression and vascular depression, 66,91,92 one for cognitive function, 66 and one for CPSP. 93 The study by Graef and colleagues 64 included data on both motor function and spasticity and, therefore, the results were independently considered for both categories.…”
Section: Resultsmentioning
confidence: 99%
“…73 Conversely, Tung and colleagues found a positive effect of rTMS on lower limb motor function, regardless of the stimulation frequency or stroke phase. 72…”
Section: Resultsmentioning
confidence: 99%
“…Restorative therapies that aim to restore the normal functioning of the neural circuits affected by stroke may have strong potential to improve post-stroke propulsion. For example, neuromodulatory treatments such as repetitive TMS and transcranial direct current stimulation can be paired with gait training interventions to augment the excitability of the lesioned corticospinal pathways [80][81][82][83][84]. Paired associative stimulation has also been used to promote targeted plasticity in corticospinal circuits in individuals with stroke and spinal cord injury [85][86][87].…”
Section: Neurophysiological Basis For Propulsion Impairmentsmentioning
confidence: 99%
“…This is in part due to the location of the lower extremity motor neurons being deeper within the brain and thus needing a more powerful magnetic field to penetrate further from the coil to elicit responses, especially in clinical populations such as stroke. Even with this knowledge, most studies using rTMS to modulate the lower extremity cortical representations have not used a double-cone coil (Tung et al, 2019). Along with the few studies measuring clinical outcomes with double-cone coil delivered rTMS post-stroke, there are even fewer studies reporting the neurophysiological changes that occur with this type of treatment (Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2012) and Kakuda et al (2013) paired rTMS with task-oriented training and reported improvements in clinical variables such as gait speed, step length, and double-support time. A promising recent meta-analysis by Tung et al (2019) showed that rTMS paired with lower extremity task-oriented training generally improved clinical outcomes (e.g., LE Fugl-Meyer, gait speed, and Berg balance) to a greater degree than training without rTMS. However, differences in rTMS protocols, task training, and coil types make it hard to form strong conclusions about the effectiveness of physical therapy augmented with rTMS.…”
Section: Introductionmentioning
confidence: 99%